The identity of Languria femoralis Motschulsky (Coleoptera: Erotylidae: Languriinae) - Gimmel, Matthew L.; Carlton, Christopher E. (Zootaxa, 2008)
In her monograph of North American Languriidae (= Erotylidae: Languriinae), Vaurie (1948) noted that Motschulsky (1860: 242) described the species Languria femoralis from New Orleans, Louisiana, but Vaurie did not examine the type. No additional information has been published on this species. The original description, reproduced here, states: